GENETIC BASIS OF HUMAN BLOOD GROUP FORMATION - Tarlykov, P.V.; Kozhamkulov, U.A.; Ramankulov, E.M. (Eurasian Journal of Applied Biotechnology, 2014)
Study of the genetic features of blood group antigens has started over 20 years ago. During this time, a variety of DNA-based methods for determining blood groups has been developed. The most significant advantage of genetic approach was to determine the blood group of the fetus in pregnancies with possible development of hemolytic disease of the fetus. At the same time the use of genetic testing with mandatory serological assay is not always necessary for the recipient. Nevertheless, the use of DNA testing to verify the phenotype can help to more accurately match donated blood for patients with a predisposition to alloimmunization, such as those who suffer from anemia. In addition, identification of the genetic structure of the loci responsible for the expression of erythrocyte antigens can help to avoid errors in determining blood groups associated with limitations of immunological methods. Therefore, the use of genetic testing will be in demand in blood transfusion centers when correct typing of a blood group with the use of agglutination method is under question.